2015
DOI: 10.1007/s12663-015-0808-z
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Le Fort Fractures at a South American Trauma Care Center: Characteristics and Management

Abstract: the most common patient with a Le Fort fracture is an adult male, with a Le Fort II fracture due to a traffic accident requiring surgical fixation on zygomaticomaxillary suture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 23 publications
2
12
1
11
Order By: Relevance
“…In our study road traffic accidents are the leading cause of orofacial injuries, which is in consonance with many of the published studies from other parts of India 5 , 6 , 7 , 8 , 9 , 10 and abroad. 11 , 12 , 13 , 14 In contrary to the results of our study, interpersonal violence was the most common cause of orofacial trauma in studies done in New Zealand, 21 North-eastern Brazil, 22 Thailand, 23 United Kingdom, 24 Australia 3 and Zimbabwe. 25 The reasons for this high frequency in Indian scenario are difficult to postulate but may be due to factors such as inadequate road safety awareness, unsuitable road conditions, violation of the speed limit and old vehicles without safety measures such as antibursts locks and energy absorbing materials.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…In our study road traffic accidents are the leading cause of orofacial injuries, which is in consonance with many of the published studies from other parts of India 5 , 6 , 7 , 8 , 9 , 10 and abroad. 11 , 12 , 13 , 14 In contrary to the results of our study, interpersonal violence was the most common cause of orofacial trauma in studies done in New Zealand, 21 North-eastern Brazil, 22 Thailand, 23 United Kingdom, 24 Australia 3 and Zimbabwe. 25 The reasons for this high frequency in Indian scenario are difficult to postulate but may be due to factors such as inadequate road safety awareness, unsuitable road conditions, violation of the speed limit and old vehicles without safety measures such as antibursts locks and energy absorbing materials.…”
Section: Discussioncontrasting
confidence: 97%
“…The predominance of orofacial injuries in the younger age group is consistent with the findings of different published work. 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 17 , 18 , 19 , 20 The male predominance in our study agrees with what is reported in the literature. 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 Males are at greater risk due to their greater participation in high risk activities, which increases their exposure to risk factors such as driving vehicles, sports that involve physical contact, an active social life and drug use, including alcohol.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This review found that Le Fort fractures required open reduction and internal fixation in 60% of cases, 30% of cases were managed conservatively, and the remaining 10% of cases required no treatment. Open fixation for Le Fort fractures at the zygomatic buttress, zygomaticomaxillary suture, and the frontozygomatic suture provides stable fixation and sufficient anatomic repositioning when indicated [22]. Le Fort fractures are frequently accompanied by fractures of the hard palate, dentoalveolar unit, and the mandible.…”
Section: Managementmentioning
confidence: 99%
“…Upon review of the literature, most Le Fort I fractures were accessed surgically through a gingivo-buccal sulcus approach, while Le Fort II and III fractures often required additional subciliary or transconjunctival approaches [4]. A coronal approach offers wide exposure of the zygomatic arch in Le Fort II and III fractures, but can result in complications secondary to the dissection of neurovascular structures [22].…”
Section: Managementmentioning
confidence: 99%